Cardiovascular disease in women with HIV-1 infection. (15th August 2017) - Volpe, Massimo; Uglietti, Alessia; Castagna, Antonella; Mussini, Cristina; Marchetti, Giulia; Bellagamba, Rita; Bini, Teresa; Mancusi, Daniela; Termini, Roberta
Abstract: Cardiovascular disease is a leading cause of death in women, nevertheless it is often underestimated in female patients without overt risk factors. The chronic infection by Human Immunodeficiency Virus (HIV) is clearly associated, along with the use of certain antiretroviral drugs and traditional risk factors, with an increased risk of cardiovascular diseases. The aim of this manuscript is to review the epidemiology, risk factors, pathogenesis, diagnostic approach, primary and secondary prevention strategies of cardiovascular disease in HIV-negative and HIV-positive female subjects. The ultimate goal is to promote knowledge and development of specific and appropriate clinical interventions and guidelines in this group of high-risk patients, mostly in view of the expected growth of ageing females with HIV.